2009
DOI: 10.3171/2009.7.peds08371
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hydrocephalus and ventriculoperitoneal shunts: influence of etiology and programmable shunts on revisions

Abstract: Object Hydrocephalus is a notorious neurosurgical disease that carries the adage “once a shunt always a shunt.” This study was conducted to review the treatment results of pediatric hydrocephalus. Methods Pediatric patients who underwent ventriculoperitoneal shunt surgery over the past 14 years were reviewed for shunt revisions. Variables studied included age at shunt placement, revision, or replacement;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 21 publications
4
82
0
Order By: Relevance
“…The investigators did not find a significant difference in shunt survival between the 3 valve types in either the short-term (Drake 1998 5 ) or extended 19 follow-up. Eleven Class II studies 4,11,15,21,23,24,27,33,36,41,44 in which differing valve types were compared also failed to demonstrate a superior valve when shunt survival was assessed. Jain et al 15 (2000) conducted a prospective cohort study in which they compared shunts using a standard differential pressure valve with a Delta (Medtronic) flowregulating valve.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigators did not find a significant difference in shunt survival between the 3 valve types in either the short-term (Drake 1998 5 ) or extended 19 follow-up. Eleven Class II studies 4,11,15,21,23,24,27,33,36,41,44 in which differing valve types were compared also failed to demonstrate a superior valve when shunt survival was assessed. Jain et al 15 (2000) conducted a prospective cohort study in which they compared shunts using a standard differential pressure valve with a Delta (Medtronic) flowregulating valve.…”
Section: Resultsmentioning
confidence: 99%
“…27 The authors found that programmable valve placement was associated with a reduced risk of both overall shunt revision (35% vs 54% in the nonprogrammable group; p = 0.016) and proximal shunt obstruction (12% vs 28% in the nonprogrammable group; p = 0.006). Notarianni et al 33 (2009) found no significant difference in a retrospective review of 253 patients who underwent shunt placement with either a programmable (Strata or Codman Hakim) or nonprogrammable (pressure-controlled or not specified) valve. The failure rate among the programmable valve group was 76.1%, and that among the differential pressure valve group was 80.0% (p = 0.11).…”
Section: Programmable Valvesmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Posthemorrhagic hydrocephalus and hydrocephalus connected with craniospinal dysraphism had significantly earlier revisions than congenital and other etiologies. 34 …”
Section: Congenital Renal Tumorsmentioning
confidence: 99%
“…However, investigators have not agreed on a clearly superior valve when used in a broad range of children with hydrocephalus. 1,[7][8][9]12,13,16,[20][21][22]29,32 Conventional NPVs require surgeons to select an optimal opening pressure before implantation. Inaccurate estimates of the shunt valve function in situ may necessitate replacement of the valve to prevent over-or underdrainage.…”
mentioning
confidence: 99%